AU-scale radio imaging of the wind collision region in the brightest and most luminous non-thermal colliding wind binary Apep. Issue 2 (16th December 2020) - Marcote, B; Callingham, J R; De Becker, M; Edwards, P G; Han, Y; Schulz, R; Stevens, J; Tuthill, P G
ABSTRACT: The recently discovered colliding-wind binary (CWB) Apep has been shown to emit luminously from radio to X-rays, with the emission driven by a binary composed of two Wolf–Rayet (WR) stars of one carbon-sequence (WC8) and one nitrogen-sequence (WN4–6b). Mid-infrared imaging revealed a giant spiral dust plume that is reminiscent of a pinwheel nebula but with additional features that suggest Apep is a unique system. We have conducted observations with the Australian Long Baseline Array to resolve Apep's radio emission on milliarcsecond scales, allowing us to relate the geometry of the wind-collision region to that of the spiral plume. The observed radio emission shows a bow-shaped structure, confirming its origin as a wind-collision region. The shape and orientation of this region is consistent with being originated by the two stars and with being likely dominated by the stronger wind of the WN4–6b star. This shape allowed us to provide a rough estimation of the opening angle of ∼150 ○ assuming ideal conditions. The orientation and opening angle of the emission also confirms it as the basis for the spiral dust plume. We also provide estimations for the two stars in the system to milliarcsecond precision. The observed radio emission, one order of magnitude brighter and more luminous than any other known non-thermal radio-emitting CWB, confirms it is produced by an extremely powerful wind collision. Such a powerful wind-collision region is consistent with Apep being a binary composed of two WR stars, so far the first unambiguously confirmed system of its kind.